2016
DOI: 10.1111/ecc.12468
|View full text |Cite
|
Sign up to set email alerts
|

Differences in survival between Māori and New Zealand Europeans with prostate cancer

Abstract: This study aims to examine the survival disparity between Māori men and New Zealand (NZ) Europeans diagnosed with prostate cancer. We identified men aged 40+ years in the Midland Cancer Network region registered with prostate cancer in 2007-2010 in the Cancer Registry. Data were extracted from patient notes of all Māori men and a sample of NZ Europeans. The survival disparity between Māori men and Europeans was estimated by the Kaplan-Meier method and Cox proportional-hazards regression models after adjusting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 18 publications
1
4
0
Order By: Relevance
“…Māori men demonstrated markedly lower scores in both the physical, and mental health scores, suggesting a poorer perceived health status and QoL compared to their non-Māori counterparts. These disparities are consistent with previous ndings on survival differences and unmet healthcare needs between these two groups (9,11) . This may be attributed to biological differences, variations in treatment choices, and disparities in access to or utilization of supportive care services (12) .…”
Section: Discussionsupporting
confidence: 93%
“…Māori men demonstrated markedly lower scores in both the physical, and mental health scores, suggesting a poorer perceived health status and QoL compared to their non-Māori counterparts. These disparities are consistent with previous ndings on survival differences and unmet healthcare needs between these two groups (9,11) . This may be attributed to biological differences, variations in treatment choices, and disparities in access to or utilization of supportive care services (12) .…”
Section: Discussionsupporting
confidence: 93%
“…Of these, 50 studies were retrospective [ 3 , 20 31 , 33 41 , 43 63 , 65 , 70 , 71 , 73 , 78 – 80 ], 3 were prospective [ 42 , 64 , 77 ], and 1 was mixed (prospective and retrospective) [ 32 ]. Research reported in these studies was conducted in the United States (US) ( n = 51) [ 3 , 20 27 , 29 61 , 63 65 , 70 , 71 , 73 , 77 , 78 , 80 ], Europe ( n = 1) [ 62 ], Asia ( n = 1) [ 79 ], and Oceania ( n = 1) [ 28 ]. The commonly reported racial groups discussed across these studies were Black (i.e., Black, Non-Hispanic Black), White (i.e., White, Non-Hispanic White, Non-Black), Hispanic 1 , Asian (i.e., Asian, Non-Hispanic Asian, Asian/Pacific Islander), and American Indian/Alaska Native (AI/AN) (i.e., AI/AN, Native American).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty-seven [ 20 , 22 , 25 , 27 , 30 , 31 , 33 36 , 38 , 41 , 48 , 49 , 51 58 , 60 , 62 , 70 , 71 , 78 ] of the 54 studies reported results on overall survival (OS) or all-cause mortality, 11 studies [ 21 24 , 26 , 31 , 37 , 38 , 44 , 50 , 61 ] reported results on prostate cancer specific mortality (PCSM), and 11 studies [ 29 , 32 , 39 , 46 , 62 65 , 73 , 77 , 80 ] reported results on OS or PCSM in patients on specific mPC treatments, with some of the studies reporting on more than one survival outcome. Nine studies [ 3 , 28 , 40 , 42 , 43 , 45 , 47 , 59 , 79 ] reported only descriptive data, described racial groups other than Black, White, Hispanic, Asian, or Native American, such as Maori, Thai, Malaysian, or conducted separate analyses within each racial group. An overview of these studies is included in Table A.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Disparate health outcomes for NZ M aori and the complex role of social determinants of health are well described in the literature. For example, M aori have lower life expectancy, 53 and more M aori than non-M aori experience socioeconomic deprivation and barriers to accessing healthcare, including culturally appropriate care. [5][6][7]54 Our findings add to the literature by demonstrating how the extent of health inequities for M aori also include the experience of critical illness.…”
Section: Discussionmentioning
confidence: 99%